IMPLEMENTASI PERATURAN DAERAH PROVINSI RIAU NOMOR 3 TAHUN 2013 TENTANG HAK DASAR ANAK (Studi Kasus di Kota Pekanbaru) - ", Wirnasari; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pekanbaru city is one of the Big Cities in Indonesia is the center of all activities of economic, social and cultural. Pekanbaru city grow well and even become centers of economic growth. The rapid development such as the establishment of offices, shopping centers, a means of connecting, factories, entertainment facilities and so inevitably encourage urban to tempt fate.However, with the development of the city of Pekanbaru, the question that arises is the gap or inequality of rights is a deepening of the division of revenues between the various income groups, between urban and rural areas. This also means that the rapid economic growth has not succeeded in tackling the problem of poverty, such as unemployment, workers minors. Therefore, the Riau provincial government issued Riau Provincial Regulation No. 3 of 2013 on Protection of Basic Rights of the Child.The concept of the theory that the Researchers use a concept implementations. implementation in principle is a way for a policy can Achieve its objectives . To implement public policy , there are two options available Immediately measures are implemented in the form of program or through policy formulation devirat or derivatives of such public policyThis study uses qualitative research methods with an assessment of descriptive data. In collecting the data, the Researchers use interviewing techniques, observation and study of literature . By using key informants and informant aftershocks as resources.These results indicate that the Riau Provincial Regulation No. 3 of 2013 on Protection of Basic Rights of the Child assessed well implemented. it can be seen from the number of Children's Child Exploitation and neglect in the city of Pekanbaru.Keywords: Impementasi and Basic Rights of the Child